Activated-carbon-supported K–Co–Mo catalysts for synthesis of higher alcohols from syngas. Issue 5 (28th May 2015) - Lv, Meimei; Xie, Wei; Sun, Song; Wu, Gaimei; Zheng, Lirong; Chu, Shengqi; Gao, Chen; Bao, Jun
<x xml:space="preserve">Abstract</x> Activated-carbon-supported K–Co–Mo catalysts exhibit excellent performance for alcohol synthesis from CO hydrogenation, especially increasing the selectivity for C2+OH significantly.